Effects of mental fatigue on psychophysiological responses, kinematic variables and technical actions in small-sided soccer games: a time course analysis - Soylu, Y.; Arslan, E.; Akçay, N.; Akgul, M. S.; Kilit, B.; Lopes, T. R.; de Lima-Junior, D. (Frontiers in Psychology, 2025)
The study compares the effects of different cognitive task durations to induce MF on 4-a-side small-sided soccer games (SSGs) in psychophysiological responses, kinematic profile, and technical performance. Sixteen young soccer players (age: 15.2±0.4years) randomly performed the mental fatigue (MF) conditions (30-, 45-, and 60-min Stroop Task) and CON sessions (30-, 45-, and 60-min documentary) immediately before a 4-a-side SSGs (4×4min, and 4min rest). Kinematic profiles were analysed with GPS. Heart rate (HR), the rating of perceived exertion (RPE), MF visual analogue scale, enjoyment, and technical performance were assessed during SSGs. The manipulation checks revealed that players experienced increased MF levels in all MF inducement durations compared with the CON [30-min, CI95%diff =5.40 (3.20 to 7.50), p <0.001; 45-min, CI95%diff =8.30 (6.00 to 10.50), p <0.001; and 60-min, CI95%diff =12.3 (10.00 to 14.50); p <0.001]. Technical performance varied with the duration of MF exposure. Successful pass presented higher values for the CON condition in the 30-min [CI95%diff =0.68 (0.21 to 1.16); p =0.035], but remained similar for the 45- [CI95%diff =-0.45 (-1.17 to 0.26); p =0.523], and 60-min [CI95%diff =0.67 (-0.08 to 1.43); p =0.401]. For the unsuccessful pass the CON condition presented lower values in the 30-min [CI95%diff =-2.36 (-2.89 to -1.83); p <0.001] and 60-min [CI95%diff =-2.80 (-3.63 to -1.97); p <0.001], but remained similar for the 45- [CI95%diff =-0.47 (-1.03 to 0.09); p =0.413]. Regarding the one-touch pass, the CON condition presented higher values in the 30- [CI95%diff =0.63 (0.31 to 0.94); p <0.001], 45- [CI95%diff =2.21 (1.76 to 2.64); p <0.001], and 60-min [CI95%diff =1.73 (1.26 to 2.19); p <0.001]. The findings of this study show that the different durations of cognitive tasks significantly affected several internal load metrics and technical performance, but not external load metrics. Understanding the effects of different cognitive task durations during SSGs allows coaches and sports scientists to customize training and recovery programs better, potentially improving player performance.